The Extent to Which Judicial Accountability Procedures Can Be Applied in Iraqi Courts to Adjudicate Private Claims and Disputes and Financial Violations - Muttair, Hazem Ali; Mhalhal, Fraq Abdulaal; Fadhil, Suhair Kadhim (American Journal of Economics and Business Management, 2022)
The research aims to verify the extent to which judicial accounting can be applied in the Iraqi environment and its relationship to traditional accounting and the difference between them, as well as to verify the extent to which courts in Iraq rely on forensic and legal accountants when considering cases of irregularities and financial disputes. In order to explain the research problem and achieve its objectives, the descriptive analytical approach was adopted, as (75) questionnaires were distributed to the sample members (auditors, accountants, chartered accountants, and financial analysts) and using the simple linear regression model scale, the research hypotheses were tested, and the research reached the most critical conclusions: There is an apparent weakness among some employees of the judiciary in Iraq, regarding the importance of judicial accountability, which affects the separation of financial violations. Therefore, the most critical recommendation is to establish a separate entity for forensic accountants in Iraq to know them and use them to help provide legal support to the courts in Iraq when presenting disputes and financial irregularities.